Предмет: Алгебра,
автор: царевич1
помогите 12-х(х-3)=(6-х)(х+2)
Ответы
Автор ответа:
4
Решение:
12-х(х-3)=(6-х)(х+2)
12-х²+3х=6х-х²+12-2х
-х²+3х-6х+х²+2х=12-12 (квадраты уходят)
х=0
Вроде решение такое.
12-х(х-3)=(6-х)(х+2)
12-х²+3х=6х-х²+12-2х
-х²+3х-6х+х²+2х=12-12 (квадраты уходят)
х=0
Вроде решение такое.
Похожие вопросы
Предмет: История,
автор: samusdasa099
Предмет: Алгебра,
автор: miixxx
Предмет: Українська література,
автор: Warlord8567474
Предмет: Математика,
автор: omarkifanuri
Предмет: Биология,
автор: inbox61